PROMOÇÃO DE SAÚDE E EDUCAÇÃO NUTRICIONAL COM ESCOLARES NA REGIÃO FRONTEIRIÇA BRASIL/BOLÍVIA - NATHALIA MENEZES DE OLIVEIRA COBELLAS (2023)
This research is linked to the Health and Work Research Line of the Border Population, of the Postgraduate Program in Border Studies at the Federal University of Mato Grosso do Sul. Its general objective was to: Identify the anthropometric profile and prevalence of overweight and obesity, as well as malnutrition, in schoolchildren in the municipal network of Corumbá – MS. The research was quantitative-qualitative in nature, as it used the documentary category and data collection, seeking a concrete interpretation of the reality studied. To this end, a theoretical framework was used to allow analyzing, sustaining and consolidating the results of the data obtained through Anthropometric Assessment. The results indicate that although there is a predominance of eutrophy, there are cases of overweight, obese and underweight children, reinforcing the importance of nutritional education in schools. Keywords: School Meals; Obesity; Malnutrition.